Real-world data mining : applied business analytics and decision making - Delen, Dursun (Upper Saddle River, New Jersey : Pearson Education LTD, 2015)
A complete data mining framework: processes, methods, techniques, evaluation, tools, and more, Up-to-date primers on text/web mining, sentiment analysis, and Big Data, Demystifies complex concepts with easy tutorials and modern case studies, For managers, analytics team members, certification candidates, and students, To make the best possible decisions, you need insights you can only uncover through data mining and business analytics. Now, renowned expert Dr. Dursun Delen explains everything you need to capture and leverage these insights, whether you're part of an analytical team or you consume its outputs. Drawing on decades at the forefront of research and instruction in the field, Delen illuminates its care principles, best practices, and key applications in areas from marketing and finance to defense. He clarifies its dense jargon, shows how its technologies fit together, identifies obstacles to success, and helps you overcome them. His plain-English, step by step explanations demystify everything from workflows to algorithms. Best of all, he shares indispensable practical guidance for maximizing your effectiveness, every step of the way. Book jacket.
Includes bibliographical references and index.
Keywords: Data mining; Big data